Vascular Lesions Treatment by Multiplex Technology - Mahmmed, Huda Hisham; Mane, Noor Riad; Ibrahim, Kadim Mohammed; Abdulwahed, Zaid Raid (Innovative: International Multidisciplinary Journal of Applied Technology (2995-486X), 2024)
This project presents an introduction to laser multiplex technology used for treating vascular lesions. This study examines aims to treat port-wine stains more effectively than conventional methods. Both high-powered 585nm pulsed dye laser and 1064nm Nd: YAG laser wavelengths are used to treat two cases of Port-wine stains at early and mature state. The Multiplex technology enables the sequential emission of the two wavelengths from one delivery system for optimized clinical effectiveness.